PENINGKATKAN KEMAMPUAN KOGNITIF MELALUI MEDIA LOOSE PART PADA ANAK USIA 5-6 TAHUN DI KB NURUL ULUM LAMPEJI MUMBULSARI TAHUN 2025-2026 - Zulfa Rifqiah; M. Fadil Djamali; Muhammad Agus Sugiarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the cognitive skills of youngsters aged 5-6 years by incorporating loose parts into learning exercises. The research method used in this study is Classroom Action Research (CAR), which is based on the Kemmis and McTaggart model and consists of four stages: preparation, implementation, observation, and reflection. The research was conducted in two cycles that included preparation, activity, observation, and reflection stages. The investigation was carried out in two stages involving children between five and six years old years as the study subjects. The use of loose parts used in this study include natural materials, recycled materials, textiles, and wooden materials to stimulate children's creativity and encourage them to generate new ideas during play. The study's conclusions show that the application of loose parts effectively improves children’s cognitive abilities, as evidenced by increased analytical thinking, inventiveness, and problem-solving skills Therefore, loose parts can be regarded as an effective alternative learning medium to improve early childhood cognitive development.